2023
DOI: 10.3389/fenvs.2023.1154739
|View full text |Cite
|
Sign up to set email alerts
|

Combination of ozone-based advanced oxidation process and nanobubbles generation toward textile wastewater recovery

Abstract: The intricate nature of various textile manufacturing processes introduces colored dyes, surfactants, and toxic chemicals that have been harmful to ecosystems in recent years. Here, a combination ozone-based advanced oxidation process (AOP) is coupled with a nanobubbles generator for the generation of ozone nanobubbles (NB) utilized the same to treat the primary effluent acquired from textile wastewaters. Here we find several key parameters such as chemical oxygen demand ammonia content (NH3), and total suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…It is worth mentioning that NB technology operates based on the occurrence of cavitation, which results from a significant decrease in pressure within the flow. Our previous research has demonstrated that our system achieved a cavitation number ( Cv ) of around 0.909 . According to Saharan et al, the cavitation phenomenon typically occurs when Cv ≤ 1. …”
Section: Methodsmentioning
confidence: 83%
See 3 more Smart Citations
“…It is worth mentioning that NB technology operates based on the occurrence of cavitation, which results from a significant decrease in pressure within the flow. Our previous research has demonstrated that our system achieved a cavitation number ( Cv ) of around 0.909 . According to Saharan et al, the cavitation phenomenon typically occurs when Cv ≤ 1. …”
Section: Methodsmentioning
confidence: 83%
“…The oxidative agent was modified using a hydrodynamic cavitation process taking place in the NB generator. Initially, the pressurized ozone was injected into the water flow, following the methodology described in the previous studies. ,, The multiphase flow, consisting of ozone and water, passed through the honeycomb structure of the NB generator. As the multiphase flow traversed the honeycomb structure, the breakdown of the flow led to the subsequent formation of ozone NBs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these 21 papers, eight measured NBs concentration in the solution. ,,, However, these studies did not report the background particle levels, potentially overestimating the actual NBs concentration. Only six studies measured and reported the surface charge of ozone NBs. ,,, Notably, none of the reviewed studies investigated the concentration change over time or the long-term stability of the ozone NBs. Only one study monitored the stability of ozone NBs in ultrapure water at pH 7–7.5, with the longest storage time being 14 days .…”
Section: Introductionmentioning
confidence: 99%